PERSEPSI MASYARAKAT TERHADAP NARAPIDANA RENTAN: IMPLIKASI TERHADAP REINTEGRASI SOSIAL - Hutapea, Israim Immanuel; Subroto, Mitro (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
This study investigates societal perceptions of vulnerable inmates and their implications for social reintegration. The urgency of this research stems from the growing need to understand how public attitudes affect the reintegration process of vulnerable populations, particularly those who have faced discrimination. A qualitative approach was employed, utilizing interviews and surveys with community members and stakeholders. Findings indicate that negative perceptions significantly hinder reintegration efforts, leading to social stigma and isolation for vulnerable inmates. The study concludes that enhancing public awareness and fostering positive narratives are essential for improving reintegration outcomes for these individuals.Keywords: societal perceptions; vulnerable inmates; social reintegration; stigma; public awareness.